Hepatitis C in a new therapeutic era: Recontextualising the lived experience. Issue 13 (23rd October 2017) - Whiteley, David; Whittaker, Anne; Elliott, Lawrie; Cunningham‐Burley, Sarah
Abstract : Aims and objectives: To explore the experience of adults living with hepatitis C in a new era of interferon‐free treatment. Background: Hepatitis C is a leading cause of morbidity and mortality worldwide, posing a significant challenge to global public health. Historically, the treatment of hepatitis C was poorly efficacious and highly demanding; however, more effective and tolerable therapies have become available in high‐income nations in recent years. This is the first study to explore how these significant developments in the treatment of hepatitis C may have influenced the experience of those living with the virus, and their understanding of the disease. Design: A qualitative study underpinned by social phenomenological theory. Methods: Data were generated through semi‐structured interviews with a purposive sample of 20 hepatitis C positive adults living in a large city in Scotland. Results: Thematic analysis identified three overriding themes. "Positioning hepatitis C" illustrated how the disease was understood within wider sociocultural, medical and politico‐economic contexts. "Beyond a physical burden" emphasised the emotional aspect of infection, and "a new uncertainty" revealed participants' cautious response to the advances in hepatitis C therapy. Conclusions: Interthematic discourse portrayed the new era of hepatitis C treatment as holding little sway over constructions of the illness, as narratives resonated with previous studies. Such unmoving "lay" understandings of hepatitis C may pose potential barriers to the new therapeutic era from reaching its full potential. Relevance to clinical practice: How people living with the virus perceive and understand hepatitis C can have an adverse impact on their engagement with care and treatment. Whilst global medical discourse eulogises the arrival of a new era of therapy, there remain significant challenges for nurses engaging those with hepatitis C in therapeutic pathways.